Aged polylactic acid microplastics with ultraviolet irradiation stunted pakchoi (Brassica chinensis L.) germination and growth with cadmium in hydroponics - Lei Sun; Ya Liu; Yakun Feng; Zequn Fan; Lei Jiang; Can Lu; Cuiling Jiang (Ecotoxicology and Environmental Safety)
The presence of biodegradable microplastics (BMPs) alongside toxic metals in soil significantly threatens plant health. Current research mainly focuses on the effects of original BMPs. In contrast, the specific impacts of ultraviolet (UV)-aged BMPs and their interaction with Cadmium (Cd) on seed germination and growth are unclear. Therefore, this study incubated aged polylactic acid (PLA) MPs through a UV irradiation aging process and used an indoor hydroponic experiment to systematically investigate the single and combined effects of Cd and BMPs (virgin and aged) on pakchoi (Brassica chinensis L.) germination, photosynthesis, antioxidant systems, and Cd accumulation. The results showed that after 21 days of UV irradiation (UPLA MPs), PLA MPs formed a fractured surface, demonstrating more detrimental effects on pakchoi than virgin ones. UPLA MPs and Cd alone inhibited pakchoi germination, growth, and photosynthesis, while PLA MPs alone promoted these processes. Combined treatment with Cd and UPLA MPs significantly increased oxidative damage and reduced pakchoi root length, chlorophyll, Mg, Mn, and Zn content. Under the combination of Cd and BMPs, PLA MPs could effectively alleviate the toxic effect of Cd on pakchoi. The results unraveled here emphasized that UPLA MPs, especially aged BMPs, could trigger adverse effects on agro-systems with heavy metals. Therefore, the results of this study can provide a new perspective and reference for the ecological risk evaluation of Cd and BMPs pollution in agricultural soils.